Development and Performance Evaluation of Power Operated Plant Peeler - ATHIRA V.A JASIDA KHALID JISMI JOB JOHNSY K.J JUGNU HAMEED; Dr. Rajesh G.K (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and Performance Evaluation of Power Operated Plant Peeler
Development and Performance Evaluation of Power Operated Plant Peeler